THE INFLUENCE OF DIFFERENT TYPES OF TASKS AND USER EXPERIENCE LEVELS ON HUMAN-COMPUTER TRUST IN THE CHATGPT APPLICATION - Rizalmi, Sigit Rahmat; Leksono, Vridayani Anggi; Karim, Abdul Alimul; Chairunnisaa, Syarifah; Anwar, Putri Gesan Prabawa (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
This study investigates the role of user experience and task type on Human-Computer Trust in the ChatGPT system. The method used in this research is an experiment where respondents are asked to do mathematics, descriptive, translation, and programming tasks on the ChatGPT application. After completing each task given, respondents were asked to fill out the trust questionnaire that had been prepared. Respondents in this study were divided into two categories: novice and expert. The total number of respondents in this study was 32 respondents. The result of this research is that the level of user experience significantly influences human-computer trust in the ChatGPT application in Task 1, Task 2, Task 3, and Task 4. However, there is no significant influence from differences in the types of tasks on human-computer trust in the ChatGPT application.